A prospective study of one‐carbon metabolism biomarkers and cancer of the head and neck and esophagus. Issue 4 (7th July 2014) - Fanidi, Anouar; Relton, Caroline; Ueland, Per Magne; Midttun, Øivind; Vollset, Stein Emil; Travis, Ruth C.; Trichopoulou, Antonia; Lagiou, Pagona; Trichopoulos, Dimitrios; Bueno‐de‐Mesquita, H B(as); Ros, Martine; Boeing, Heiner; et al.
<x xml:space="preserve">Abstract</x> Experimental and epidemiological data suggest that factors of one‐carbon metabolism are important in the pathogenesis of several cancers, but prospective data on head and neck cancer (HNC) and esophagus cancer are limited. The European Prospective Investigation into Cancer and Nutrition (EPIC) study recruited 385, 747 participants from 10 countries who donated a blood sample. The current study included 516 cancer cases of the head and neck and esophagus and 516 individually matched controls. Plasma levels of vitamins B2, B6, B9 (folate), B12, and methionine and homocysteine were measured in pre‐diagnostic plasma samples and analyzed in relation to HNC and esophagus cancer risk, as well as post‐diagnosis all‐cause mortality. After controlling for risk factors, study participants with higher levels of homocysteine had elevated risk of HNC, the odds ratio (OR) in conditional analysis when comparing the top and bottom quartiles of homocysteine [ORQ4vs. Q1] being 2.13 (95% confidence interval [95% CI] 1.13–4.00, p for trend 0.009). A slight decrease in HNC risk was also seen among subjects with higher levels of folate (ORQ4vs. Q1 0.63, 95% CI 0.35–1.16, p for trend 0.02). Subgroup analyses by anatomical sub‐site indicated particularly strong associations with circulating homocysteine for oral cavity and gum cancer (p for trend 8 × 10−4), as well as for oropharynx cancer (p for trend 0.008). Plasma concentrations of the other investigated biomarkers did not display any clear association with risk or survival. In conclusion, study participants with elevated circulating levels of homocysteine had increased risk of developing squamous cell carcinoma of the head and neck.